Strategic Policy of Coastal Sustainability based on Local Conditions and Needs in Sambas Regency, West Kalimantan - Nurliza Nurliza; Eva Dolorosa; Agusmini Erawati (Universitas Muhammadiyah Yogyakarta, 2018)
Recently, there has been a growing controversy on strategic policy issues in coastal areas. Coastal regions have the most diverse, complex, and productive ecosystems due to demographic and economic pressure. This ecosystems are important for food security. On the other hand, coastal problems are national issues, not just state or local issues. This research aims to propose the priority dimension of a stakeholder role in a strategic policy to promote the coordination and sustainability of socioeconomic activities in coastal areas involving stakeholders as primary data, i.e. fishermen, merchants, private, and government using SUSTAIN indicators with AHP and Rap-Coastal methods. The result reveals that governance dimension was still the most priority and the most sustainable index to achieve policies; monitoring tools; human resources capacity building, implementation of good management practices; and public participation. Meanwhile, social well-being dimension was the most priority to achieve the economy through transportation; and attaining the goal of equity was the priority for government policy. There are three sensitive aspects of coastal sustainability management, including integrated program, identified parties actively informed and involved, and partnership between local governments and communities.